Let's fill in the blanks for each expression:
-
For \( y^{-6} \): \[ y^{-6} = \frac{1}{y^{6}} \] So, the first blank is 6.
-
For \( p^{0} \): \[ p^{0} = 1 \quad \text{(as long as } p \neq 0\text{)} \] The blank here is 1.
-
For \( u^{-12} - r^{-5} \): \[ u^{-12} = \frac{1}{u^{12}} \quad \text{and} \quad r^{-5} = \frac{1}{r^{5}} \] Thus: \[ u^{-12} - r^{-5} = \frac{1}{u^{12}} - \frac{1}{r^{5}} \] Using the same format as given, we can rewrite it as: \[ \frac{1}{u^{12}} - \frac{1}{r^{5}} \] So, the blanks are 12 and 5 respectively.
Putting it all together:
- \( y^{-6} = \frac{1}{y^{6}} \)
- \( p^{0} = 1 \) (where \( p \neq 0 \))
- \( u^{-12} - r^{-5} = \frac{1}{u^{12}} - \frac{1}{r^{5}} \)
Thus, the final answers are:
- 6
- 1
- 12 and 5.